International Oil Trade, Global Geopolitical Risk, and the Dynamics of Energy Diplomacy - Sahaidak, Mariia (2024)
Oil is susceptible to various geopolitical events, which have a potential to disrupt the export and import of key energy commodity. The Middle East and North Africa have a broader impact on the international oil trade. The goal of this thesis is to explore the intricate dynamics of the trade relationship of the most strategically important energy titans of the MENA region using the Gravity model of trade. By addressing the impacts of geopolitical risks and oil price volatility – this thesis will be able to evaluate the impact of global geopolitical risk on cross-countries trade. By examining the volatility of the oil prices on geopolitical tensions and political disagreements, the research will be able to evaluate the effectiveness of energy diplomacy on oil supply and demand balance following the geopolitical disruptions, and the effectiveness of energy policy formulations.